2002
DOI: 10.1002/1521-396x(200208)192:2<377::aid-pssa377>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Structural Properties of GaN Pendeo-Epitaxial Layers

Abstract: The effects of growth parameters on growth behavior of Pendeo‐epitaxial GaN layers in 〈1$ \bar 1 $00〉 patterned GaN seed stripes on sapphire were systematically investigated to improve the structural properties of the overgrown layers. It was found that the ratio of lateral to vertical growth rate (γ) is strongly affected by changes in growth temperature, reactor pressure, and V/III ratio, which have an effect on the distribution of crystallographic tilt among the wing regions. Also, the crystallographic aniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…2(d). However, the growth conditions with the triangular GaN films cause the retardation of the coalescence of the wing region and the crystallographic tilting [8]. Because the bending of threading dislocations is mostly accomplished at the initial growth, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2(d). However, the growth conditions with the triangular GaN films cause the retardation of the coalescence of the wing region and the crystallographic tilting [8]. Because the bending of threading dislocations is mostly accomplished at the initial growth, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The regrowth at the lower temperature resulted in the retardation of the coalescence of wing regions (window region) and must perform thick film growth for the complete coalescence on the surface. Also, it has been reported that the decrease of the γ ratio increased the degree of crystallographic tilt [8]. Therefore, most of the regrowth should be deposited at higher temperature and lower reactor pressure for the promotion of lateral growth.…”
Section: Methodsmentioning
confidence: 99%
“…The large height of the stripes, as well as the intervals between them provides much space for lateral growth of GaN. Thus it should be possible to obtain low-dislocation material in the form of stripes, wider than those reported by other authors [1][2][3][4][5]. Low-dislocation stripes width is crucial for the production of high-power laser diodes.…”
Section: Article In Pressmentioning
confidence: 86%
“…The most widely used methods are ELOG [1,2] and pendeoepitaxy [3][4][5]. However, they provide low-dislocation-density material in the form of stripes of 3-5 mm which is insufficient for high-power laser diodes.…”
Section: Introductionmentioning
confidence: 99%
“…That means that the crystallo- graphic tilts of wing layers did not occur during their overgrowths. It is known that the crystallographic tilt is strongly affected by the ratio of the lateral to vertical growth rate (g) under various growth conditions such as growth temperature, reactor pressure and V/III [9]. In the case of relatively high g (g > 2) or low g (g < 0.7), the tilt at wing regions was dramatically decreased.…”
mentioning
confidence: 95%